Microdosing of nitrogen fertiliser and cattle manure under in situ rainwater harvesting to improve maize production in smallholder farming system in a semiarid area of Zimbabwe - Kugedera, Andrew T.; Kokerai, Leticia K. (Journal of Sustainable Agriculture and Environment, 2023)
Introduction: Maize production in smallholder farmers located in semiarid areas of Zimbabwe are mainly constrained by soil moisture and nutrient stress. Moisture stress is mainly due to erratic rainfall, high rates of evapotranspiration and limited knowledge of the use of in situ rainwater harvesting (IRWH) techniques. Tied ridges (TRs) are one of the best IRWH techniques which have good potential in mitigating climate change. Materials and Methods: The study used TR, planting pit (PP) and conventional tillage (CT) as main factors and four rates (0, 29.25, 58.5 and 89.5 kg N ha−1) of nitrogen (N) as subplot factor. Soil organic carbon and available phosphorous were determined using Oslen method where soils were incubated for 2 h at 110°C. Smallholder farmers are limited to apply large quantities of nutrients hence the need for microdosing. The study objective was to evaluate the effects of nutrient microdosing and IRHW techniques on maize grain yield, rainwater use efficiency (RWUE), nitrogen use efficiency (NUE) and return on investment in semiarid areas of Zimbabwe. Results: Interaction of TR and N microdosing significantly (p < 0.05) improved maize grain yields. IRWH also showed significant effects (p < 0.05) on maize grain yields with a trend: TR > PP > CT. RWUE and NUE were significantly (p < 0.05) improved with the interaction of IRWH and N. Application of 58.5 kg N ha−1 had the highest NUE under TR. TR had the highest (US$1747.23) return on investment when combined with 89.5 kg N ha−1 during 2021/22 cropping season. Conclusion: The use of TR and 89.5 kg N ha−1 proved to be a potential strategy in increasing maize grain yields, produce higher return on investment and increase RWUE. The use of TRs and 89.5 kg N ha−1 is recommended because of high maize grain yield, RWUE and return on investment. KEYWORDS in situ rainwater harvesting, microdosing, nitrogen use efficiency, return on investment, semiarid areas
Keywords: Rainwater harvesting; Maize production; Nutrient microdosing